CERAMICS ANTENNA THE FUTURE OF WIRELESS TECHNOLOGY - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, December 2015 – The rapid development in wireless technology has currently forced the research on antenna technology to look into the techniques and design of antennas of various sizes to suit the existing technological advancements.